About the necessity of scientific research concerning regional and ethnoregional parties in Central and Eastern Europe - Myśliwiec, Małgorzata (Political Preferences, 2016)
The history of states situated in Central and Eastern Europe in nineteenth and twentieth centuries differs significantly from the history of contemporary them western democracies. Problems of decentralization and implementation of minorities rights was a democratic experiment between two world wars, without time for its consolidation. Also it was not a political priority for elites ruling between 1945 and 1989, nor even after the beginning of the democratic transition. Mentioned problems have decisively caused difficulties in defining relations between political centres and peripheries in states of Central and Eastern Europe, in the period of the political transition in the last decade of the twentieth century. However, it does not mean that politically significant processes in these states are taking place only in political centres and their only actors are state-wide-parties. For that reason the main aim of this paper will be to justify the necessity of scientific research concerning regional and ethnoregional parties as well as proto-parties in Central and Eastern Europe. Key words: political parties, regional parties, ethnicity, regionalism, Central and Eastern Europe